Compressive Strength Development of Seawater-Mixed Concrete Subject to Different Curing Regimes - Khatibmasjedi, Morteza; Ramanathan, Sivakumar; Suraneni, Prannoy; Nanni, Antonio (ACI materials journal, 2020)
The use of seawater as mixing water in reinforced concrete (RC) is currently prohibited by most building codes due to potential corrosion of conventional steel reinforcement. The issue of corrosion can be addressed by using noncorrosive reinforcement, such as glass fiber-reinforced polymer (GFRP). However, the long-term strength development of seawater-mixed concrete in different environments is not clear and needs to be addressed. This study reports the results of an investigation on the effect of different environments (curing regimes) on the compressive strength development of seawater-mixed concrete. Fresh properties of seawater-mixed concrete and concrete mixed with potable water were comparable, except for set times, which were accelerated in seawater-mixed concrete. Concrete cylinders were cast and exposed to subtropical environment (outdoor exposure), tidal zone (wet-dry cycles), moist curing (in a fog room), and seawater at 60[degrees]C (140[degrees]F) (submerged in a tank). Under these conditions, seawater-mixed concrete showed similar or better performance when compared to reference concrete. Specifically, when exposed to seawater at 60[degrees]C (140[degrees]F), seawater-mixed concrete shows higher compressive strength development than reference concrete, with values at 24 months being 14% higher. To explain strength development of such mixtures, further detailed testing was done. In this curing regime, the seawater-mixed concrete had 33% higher electrical resistivity than the reference concrete. In addition, the reference concrete showed calcium hydroxide leaching, with 30% difference in calcium hydroxide values between bulk and surface. Reference concrete absorbed more fluid and had a lower dry density, presumably due to greater seawater absorption. Seawater-mixed concrete performed better than reference concrete due to lower leaching because of a reduction in ionic gradients between the pore solution and curing solution. These results suggest that seawater-mixed concrete can potentially show better performance when compared to reference concrete for marine and submerged applications. Keywords: compressive strength; durability; electrical resistivity; formation factor; seawater; thermogravimetric analysis.